Mental Health Consequences of Childhood Physical Abuse in Chinese Populations: A Meta-Analysis. (December 2016) - Ip, Patrick; Wong, Rosa S.; Li, Sophia L.; Chan, Ko Ling; Ho, Frederick K.; Chow, Chun-bong
Objective: Childhood physical abuse (CPA) can lead to adverse mental health outcomes in adulthood, but its potential impact on Chinese populations is still unclear. This meta-analysis is the first to examine the association between CPA and mental health outcomes in Chinese populations. Study Design: Studies published before December 31, 2014 were identified from Embase, CINAHL, Scopus, PsycINFO, PubMed, and Chinese National Knowledge Infrastructure databases. Studies with data on the association between CPA and mental health outcomes from Chinese subjects were included. Twenty-four studies were initially identified but two were excluded because of poor quality. Two reviewers independently extracted data to generate summary effect sizes using a random-effects meta-analytic model. A priori subgroup and sensitivity analyses were performed to evaluate heterogeneity and bias in these studies. Results: Our meta-analysis of 22 studies found a significant positive association between CPA and overall mental health outcomes among all Chinese subjects (pooled effect size: odds ratio [ OR ] = 2.16, 95% confidence interval [CI] = [1.87, 2.49]) and among community samples (pooled effect size: OR = 2.06, 95% CI [1.71, 2.48]). Based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision, diagnostic criteria, CPA was more strongly associated with Axis II ( OR = 2.62, 95% CI [2.13, 3.22]) than Axis I disorders ( OR = 1.85, 95% CI [1.58, 2.17]). Conclusions: The detrimental effects of CPA on mental health outcomes in Chinese populations were comparable to, if not more than, the West. Contrary to the Chinese belief that physical punishment is a safe way to discipline children, our findings highlight the potential harm to mental health and the need to change this parenting practice.